Advances in group processes - Thye, Shane R.; Lawler, Edward J. (Advances in Group Processes, 2021)
This volume includes papers that address theoretical and empirical issues related to occupational deference structures, emotions generated by social identities, racial threat, sticky expectations, status and response latency, race and moral expectations in employment, comparison processes and competition and models of intergroup association.